Trust and Witnessing: Lessons for Dance Education / Professional Development in Community (LEARNing Landscapes, 2015)
Dance education is rarely taught in Australian primary schools. A National Arts curriculum was published online in 2014, and ready for implementation the following year. Therefore schools and teachers will be looking for models and frameworks that will help them implement the arts, including dance. The author experienced the work of the community-based dance company Dance Exchange during a summer institute in 2013. For a teacher of dance in a relatively isolated regional town, taking part in the summer institute was a rare opportunity to nourish creative inspiration and a reminder of the importance of the collaborative creative process and the embodied experience within Dance Education.
Keywords: dance education; arts; collaboration; professional development